Energy exchange among heterogeneous prosumers under price uncertainty - Marta Castellini; Luca Di Corato; Michele Moretto; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2021)
In this paper, we provide a real options model framing prosumers' investment in photovoltaic plants. This is presented in a Smart Grid context where the exchange of energy among prosumers is possible. We determine the optimal size of the photovoltaic installations based on the influence the self-consumption profiles on the exchange of energy among prosumers. We calibrate the model using figures relative to the Northern Italy energy market and investigate the investment decision allowing for different prosumer profiles and consider several combinations of their individual energy demand and supply. Our findings show that the shape of individual energy demand and supply curves is crucial to the exchange of energy among prosumers, and that there could be circumstances under which no exchange occurs.
Keywords: Q42; C61; D81; 330; Smart Grids; Renewable Energy Sources; Real Options; Prosumer; Peer to Peer Energy Trading